The transnational drivers of populist backlash in Europe: The role of courts. Issue 2 (25th April 2019) - Pin, Andrea
Abstract: This Article explores whether and how contemporary constitutionalism may have triggered or facilitated populism and its illiberal agenda. In particular, it focuses on some of the legal doctrines that have characterized the growth of transnational and supranational judicial fora, contrasting them with populism in Europe. The Article first sketches the role of courts in shaping contemporary transnationalism and supranationalism in Europe. Then, it analyzes the role that the ideals of progress and equality have played in the judicialization of pan-European legal culture. Finally, it ponders the consequences of the constitutionalization process of European law for the role of democratically accountable institutions.